Alat Pengusir Hama Burung - Karnova Yanel (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
Pests are animals that interfere with agricultural production such as wild boars, squirrels, rats, and insects. Several types of pests often attack rice plants, causing significant losses to farmers. Therefore researchers are interested in making bird repellent devices using a microcontroller. Microcontroller is a functional computer system on a chip. It contains a processor core, memory (a small amount of RAM, program memory, or both), and input-output equipment. This program is made based on the main controller, namely the Arduino Uno Microcontroller. The programming language used is the C + language. And the program created and saved in (uno) format. This is because the Arduino Uno used is part of the Arduino microcontroller which has its own compiler called the Arduino IDE. Then this file is compiled and then uploaded to the microcontroller using a USB cable so that the microcontroller can work as desired. The working principle of this tool is that when the PIR sensor reads the movement of living creatures (bird pests), the sensor sends commands to the servo motor by detecting the body's heat temperature detected by the PIR sensor, then the servo motor will move by rotating 30 degrees to left and right. When the PIR sensor has detected living creatures nearby, the LED light used will light up as a sign that the sensor detects the body temperature of living creatures.